PENGARUH ETIKA BISNIS ISLAM TERHADAP KEUNTUNGAN USAHA PADA WIRAUSAHA DI DESA DELITUA KECAMATAN DELITUA - Desy Astrid Anindya (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2017)
According to the Islamic business ethics, every business person in trade should not merely aim at the highest possible profit, but the most important thing is to find a means to increase and reach the top of the sustenance provided by Allah SWT.The purpose of this research is to find out whether there is influence of Islamic business ethics against profit. This type of research is the associative nature of causality.This type of research is the associative nature of causality. Data retrieval using direct surveys and instruments used are questionnaire. The population is predominantly entrepreneurial principals, and sample as many as 54 respondents using accidental sampling. Analysis method used is simple linear regression.The results showed that there was influence of Islamic business ethics on the entrepreneurial efforts of profits against the village of Delitua sub-district of Delitua (p = 0.000). The conclusions of the study results is every muslim traders should run its economy activities based on Sharia rules or statutes, namely that God commanded his servants.